Adsorption mechanism of mussel-derived adhesive proteins onto various self-assembled monolayers. Issue 63 (14th August 2017) - Huang, Shizhe; Hou, Qingfeng; Guo, Donghong; Yang, Hui; Chen, Ting; Liu, Fanghui; Hu, Guangxin; Zhang, Minghui; Zhang, Jian; Wang, Jinben
Abstract : Mussel adhesion to a variety of surfaces has received considerable attention due to its ability to bind strongly to many surfaces under water. Abstract : Mussel adhesion to a variety of surfaces has received considerable attention due to its ability to bind strongly to many surfaces under water. Understanding the interactions between mussel-derived adhesive proteins and surfaces with different chemical and physical properties is of great theoretical and practical interest. Here, we explored the adsorption behavior of mussel foot protein-1 (Mfp-1) onto self-assembled monolayers (SAMs) with varying wettability and chemistry, through quartz crystal microbalance with dissipation measurements, ellipsometry, X-ray photoelectron spectroscopy, and atomic force microscopy. The results showed significant differences in the structural conformations of protein adsorbed layers for the series of surfaces. Two mechanisms were found in all the systems; in the case of hydrophobic surfaces, the first regime corresponded to the initial adsorption of protein molecules onto the surfaces, and the second kinetic process was related to conformational changes, resulting in a relatively rigid and dense protein layer; while for hydrophilic surfaces, a loose and soft adsorbed protein film was generated. It was found that the adsorbed mass of Mfp-1 at the hydroxyl terminated SAM surface was the smallest among all the modified surfaces, because of the formation of hydration layers reducing protein adhesion effectively. Furthermore, the interaction mechanisms of protein molecules with solid surfaces were suggested, providing a new way of designing and developing underwater adhesive or anti-fouling materials.